Factors Affecting Ultrasonographic Fetal Weight Estimation Accuracy in Low Birth Weight Newborns - Tuten, Nevin; Guralp, Onur; Gok, Koray; Tuten, Abdullah; Gezer, Altay (Gynecology Obstetrics & Reproductive Medicine, 2022)
Objective: To investigate the accuracy of fetal weight estimation made by the last prenatal ultrasound measurement in low birth weight newborns (<2500 g). Study Design: A total of 1082 women were evaluated in this retrospective cohort study. Demographic and clinical information of the mother and newborn and obstetric ultrasonography measurements and findings performed in the last week before birth were recorded. Accuracy of fetal weight estimation and parameters affecting it was investigated. Results: Accurate estimation rates were lower in the term compared to the preterm delivery group; and in the SGA group compared to the AGA group (respectively, p=0.016, p=0.032). Accurate estimation rates (p=0.182) were comparable between the 500-1500 g and 1501-2500 g subgroups. The multiple linear regression analysis showed that gestational age at birth, birth weight, examination during labor, and duration between examination to delivery were statistically significant for the accurate estimation(p=0.001) Conclusions: Accurate estimation rates were lower in the term compared to the preterm delivery group, and in the SGA group compared to the AGA group. The factors affecting accurate estimation were found to be gestational age at birth, birth weight, examination during labor, and duration between examination to delivery. Keywords: Accurate estimation rate, Duration between examination to delivery, Examination during